ANALISIS IMPLEMENTASI GAME EDUKASI âTHE HERO DIPONEGOROâ GUNA MENINGKATKAN HASIL BELAJAR SISWA DI MTS. ATTAROQIE MALANG - Agustina, Rini; Chandra, Ade (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2017)
The development of todays technology is impacting on the learning process in schools and also affect the learning material as well as the delivery of a material in the process of teaching and learning activities. Learning is now more attractively designed to encourage and increase student achievement.Â Â Â Â Â Â Â Â Learning the Game is one of the new methods are now starting to demand of students, the theme of the lesson give a fresh new look for students to love a subject of study. Curriculum 2013 is a competency-based curriculum.Â Â Â Â Â Â Â Â Inside was formulated in an integrated manner the attitude of competence, knowledge and skills that must be mastered learners. Also formulated learning and assessment process required learners to achieve their competencies (Minister of Education and Culture: 2014).Â Â Â Â Â Â Â Â Application educational game about the war Diponegoro intended to foster a sense of nationalism to Indonesia country. Where this educational game will be made in accordance with the times and useful as educational deployment solution that can be done anytime and anywhere.Â Keywords: Educational Games, MTs Attaroqie Malang, PHP CodeIgniter, web base